PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) OLEH DINAS KESEHATAN DI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Idriansyah "; Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine disease control Dengue Hemorrhagic Fever conducted by the Department of Health in the District of Pangkalan Kerinci, Pelalawan and to mengetaui factor of any factor that inhibits disease control Dengue Hemorrhagic Fever by Public Health Service, the concepts used in the theory proposed Lubis (2000 : 105), which expresses the control is a function that regulates and directs how the implementation of a planned program and other administrative activities, either in the form of management of the arrangements, procedures and through action to intervene to allow the optimization of the implementation of a program plan. The results of this study indicate that the development of mass media and outreach to the community about the disease Dengue Hemorrhagic Fever (DHF) in the District of PangkalanKerinci is still not good it is in because of less intensive DHO Palalawan in propagating his program, Investigations Epidemiology conducted by PHC Berseri District of Pangkalan Kerinci is good, Mobilization society through Pemberantasan mosquito nest (PSN) in the District of Pangkalan Kerinci somewhat less than effective this is due to lack of participation, Abatesasi performed by PHC Berseri District of Pangkalan Kerinci still not effective, this is due to lack of education about the use of abate to the public, Fogging is carried out by the District Health Office Palalawan still less than optimal because it is a new Pelalawan District Health Office will conduct fogging after reports an epidemiological survey conducted by Radiant Health Center District of Pangkalan Kerinci.Keywords: Control, of Dengue Haemorrhagic Fever (DHF)